A educação ambiental no ensino superior: o que dizem os professores universitários - Silva, Adriano Sotero da (2013)
The objective of this research was to understand how professors deal with environmental education in higher education. In this sense, professors were interviewed in order to understand the aforementioned discipline's trajectory in the educational field until its implementation in the formal education. The research was performed with six professors and the data was collected through interviews with professors who have been connected to environmental education. Moreover, it was possible to verify how those professors' theoretical conceptions influence in their teaching and how they understand environmental education in higher education. Taking into account that statement, the study verified that the environmental education is defined as an area that belongs to pedagogical tendencies of a paradigm complexity. In conclusion, it was realized that environmental education, as a discipline in academic training, is taught in different ways, whether by legal pressure of the formal teaching system and by professors' option to work in this field in higher education courses.